Finite difference method for numerical solution of a generalized burgers-huxley equation - Nuraisyah Mohamed Daud, 1992-, author 597380 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains) - Universiti Teknologi Malaysia, 2017